Moderation is best: effects of grazing intensity on plant–flower visitor networks in Mediterranean communities. Issue 3 (26th April 2016) - Lázaro, Amparo; Tscheulin, Thomas; Devalez, Jelle; Nakas, Georgios; Stefanaki, Anastasia; Hanlidou, Effie; Petanidou, Theodora
Abstract: The structure of pollination networks is an important indicator of ecosystem stability and functioning. Livestock grazing is a frequent land use practice that directly affects the abundance and diversity of flowers and pollinators and, therefore, may indirectly affect the structure of pollination networks. We studied how grazing intensity affected the structure of plant–flower visitor networks along a wide range of grazing intensities by sheep and goats, using data from 11 Mediterranean plant–flower visitor communities from Lesvos Island, Greece. We hypothesized that intermediate grazing might result in higher diversity as predicted by the Intermediate Disturbance Hypothesis, which could in turn confer more stability to the networks. Indeed, we found that networks at intermediate grazing intensities were larger, more generalized, more modular, and contained more diverse and even interactions. Despite general responses at the network level, the number of interactions and selectiveness of particular flower visitor and plant taxa in the networks responded differently to grazing intensity, presumably as a consequence of variation in the abundance of different taxa with grazing. Our results highlight the benefit of maintaining moderate levels of livestock grazing by sheep and goats to preserve the complexity and biodiversity of the rich Mediterranean communities, which have a long history of grazing by these domestic animals.